Is my short induction proof correct?

In summary, a short induction proof is a proof technique that uses mathematical induction to prove a statement for all values of a variable. It differs from a regular induction proof in that it only requires one or a few steps and is used for simpler statements. The key components of a short induction proof are the base case, induction hypothesis, and inductive step. To ensure the correctness of a short induction proof, all necessary components must be included and the inductive step must follow logically from the induction hypothesis. However, it is not suitable for all mathematical statements and is most commonly used for proving statements about natural numbers.
  • #1
Eclair_de_XII
1,083
91

Homework Statement


"Prove: ##∀n∈ℕ##, ##3^n>n^2##

Homework Equations

The Attempt at a Solution


(1) We will prove that ##3^n>n^2## at ##n=1##
##3=3^1>1=1^2##

(2) Now assume that ##3^k>k^2## for some ##k>1##
(3) We will prove that ##3^{k+1}>(k+1)^2## or ##3⋅3^k>k^2+2k+1##
Note that ##k^2+2k^2+1=3k^2+1≥k^2+2k+1##, and as such, ##3⋅3^k≥3k^2+3>3k^2+1≥k^2+2k+1##. So ##3^{k+1}>3k^2+1≥(k+1)^2##.

I'm basically ambivalent as to whether to insert that extra term in the inequality: ##3k^2+1##, not knowing whether it is equal to, less than, or greater than ##3^{k+1}##. Can someone check my work, please? Thanks.
 
Last edited:
Physics news on Phys.org
  • #2
Eclair_de_XII said:

Homework Statement


"Prove: ##∀n∈ℕ##, ##3^n>n^2##

Homework Equations

The Attempt at a Solution


(1) We will prove that ##3^n>n^2## at ##n=1##
##3=3^1>1=1^2##

(2) Now assume that ##3^k>k^2## for some ##k>1##
(3) We will prove that ##3^{k+1}>(k+1)^2## or ##3⋅3^k>k^2+2k+1##
Note that ##k^2+2k^2+1=3k^2+1≥k^2+2k+1##, and as such, ##3⋅3^k≥3k^2+3>3k^2+1≥k^2+2k+1##. So ##3^{k+1}>3k^2+1≥(k+1)^2##.

I'm basically ambivalent as to whether to insert that extra term in the inequality: ##3k^2+1##, not knowing whether it is equal to, less than, or greater than ##3^{k+1}##. Can someone check my work, please? Thanks.
The induction step boils down to showing that ##3k^2 > (k + 1)^2##. It's easy enough to prove the equivalent statement ##3k^2 - (k + 1)^2 > 0##.
 
  • #3
Let's see...

##3k^2-k^2-2k-1=2k^2-2k-1=2k(k-1)-1>0## for ##k>0##?
 
  • #4
Eclair_de_XII said:
Let's see...

##3k^2-k^2-2k-1=2k^2-2k-1=2k(k-1)-1>0## for ##k>0##?
Almost. 2k(k - 1) - 1 > 0 for k > 1.
If k = 0, you have 0(-1) - 1 < 0, and if k = 1, you have 2(0) - 1 < 0.
 
Back
Top